Direct and indirect plant regeneration from various explants of eastern cottonwood clones (Populus deltoides Bartram ex Marsh.) with tissue culture - (:unkn) unknown (ACADEMIC JOURNALS, 2011)
Populus species are important resource for certain branches of industry and have special roles for scientific study on biological and agricultural systems. Plant regeneration via direct and indirect organogenesis of four Populus deltoides Bartram ex Marsh. ssp. deltoides x Populus deltoides Bartram ex Marsh. ssp. deltoides hybrid clones (89 M 011, 89 M 044, 89 M 048, 89 M 066) and P. deltoides ssp. deltoides clone (Samsun) were investigated. Direct organogenesis was established from nodes and internodes on woody plant medium (WPM) supplemented with cytokinins and/or auxins. The 89 M 011 clone gave the highest percentage (100%) of regeneration on WPM with 1 mg/l zeatine from internode explants. Indirect organogenesis via callus phase was obtained from nodes and petioles on WPM supplemented with different concentrations of 2,4-Dichlorophenoxy acetic acid (2,4-D). The nodes part of the 89 M 066 clone gave the highest rate of generative callus (100%) on WPM supplemented with 2 mg/l 2,4-D. Indirect shoots were obtained from the node callus on WPM with cytokinins. There was root formation from directly regenerative shoots which were cultured on WPM or Murashige and Skoog Basal Medium (MS) containing different ratios of indole butyric acid (IBA). Rooted seedlings in vitro were successfully acclimatized. Data on in vitro study were subjected to statistical evaluation. The in vitro regeneration system will allow this study to set reliable procedures for the genus and clones.
Keywords: Poplar; tissue culture; regeneration; organogenesis; TRANSFORMATION; LEAF; ROOT